Investigation of the relationship between museums and cities in the context of image: cases from Istanbul - Ozorhon, Ilker Fatih; Ozorhon, Guliz (Journal of Architecture and Urbanism, 2015)
Whether created by transforming historic buildings, whether contemporary and new design products, museums play a key role in terms of the image and attractiveness of the city they are located in. This study investigates the relation that the museums in Istanbul have established with the city in the context of image. The method employed is to first introduce the theoretical context of the subject based on literature review; to analyze the selected museums in terms of the city-museum interaction and to evaluate the selected museums within the context of the contributions they make to the image of Istanbul by descriptive methodology. As a result, the contribution of the museums on the city and the contribution of the city on the museums have been demonstrated and the varying and symbiotic nature of this relationship has been emphasized.